Long-term Dynamical Stability in the Outer Solar System. II. Detailed Secular Evolution of Four Large Regular and Resonant Trans-Neptunian Objects - Muñoz-Gutiérrez, Marco A.; Peimbert, Antonio; Pérez-Villegas, Angeles (The Astronomical journal, 2025)
The long-term evolution of the outer solar system is subject to the influence of the giant planets, however, perturbations from other massive bodies located in the region imprint secular signatures, which are discernible in long-term simulations. In this work, we performed an in-depth analysis of the evolution of massive objects Eris, 2015 KH 162 , Pluto, and 2010 EK 139 (aka, Dziewanna), subject to perturbations from the giant planets and the 34 largest trans-Neptunian objects. We do this by analyzing 200, 1 Gyr long simulations with identical initial conditions, but requiring the numerical integrator to take different time steps for each realization. Despite the integrator’s robustness, each run’s results are surprisingly different, showing the limitations of individual realizations when studying the trans-Neptunian region due to its intrinsic chaotic nature. For each object, we find orbital variables with well-defined oscillations and limits, and others with surprisingly large variances and seemingly erratic behaviors. We found that 2015 KH 162 is a nonresonant and very stable object that experiences only limited orbital excursions. Pluto is even more stable and we found a new underlying constraining mechanism for its orbit; 2010 EK 139 is not well trapped in the 7:2 mean motion resonance in the long term and cannot be trapped simultaneously in von Zeipel–Lidov–Kozai resonance; and finally, we found that at present Eris’s longitude of perihelion is stationary, tightly librating around 190°, but unexpectedly loses its confinement, drifting away after 150 Myr, suggesting a missing element in our model.